2019
DOI: 10.1097/fjc.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

Titration and Tolerability of Sacubitril/Valsartan for Patients With Heart Failure in Clinical Practice

Abstract: Little is known about the dosing and tolerability of sacubitril/valsartan (LCZ696; Entresto, Quebec, Canada) in a nonclinical trial population. This study was conducted to evaluate the use and tolerability of sacubitril/valsartan in patients followed at a multidisciplinary heart failure (HF) clinic. We performed a retrospective chart review of 126 patients with HF, initiated on sacubitril/valsartan, and seen at a specialty HF clinic between August 1, 2015, and August 1, 2017. We defined the target dose of sacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 18 publications
4
9
0
1
Order By: Relevance
“…The low rate of sac/val target dose achievement is in line with previous reports from CHF outpatient clinics 17,18 . Nevertheless, NYHA classification and well‐being improved for both ‘Achievers' and ‘Non‐Achievers', suggesting that patients had improved well‐being and clinical stability compared with their pretrial experience regardless of sac/val target dose achievement or maintenance.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The low rate of sac/val target dose achievement is in line with previous reports from CHF outpatient clinics 17,18 . Nevertheless, NYHA classification and well‐being improved for both ‘Achievers' and ‘Non‐Achievers', suggesting that patients had improved well‐being and clinical stability compared with their pretrial experience regardless of sac/val target dose achievement or maintenance.…”
Section: Discussionsupporting
confidence: 88%
“…The low rate of sac/val target dose achievement is in line with previous reports from CHF outpatient clinics. 17,18 Nevertheless, NYHA classification and well-being improved for both 'Achievers' and 'Non-Achievers', suggesting that patients had improved well-being and clinical stability compared with their pretrial experience regardless of sac/val target dose achievement or maintenance. In addition, when comparing with the 6 months period preceding the trial, less healthcare utilization was observed with sac/val treatment on both 'Achievers' and 'Non-Acievers', which is in accordance with a reduced number of unplanned rehospitalizations found in PARADIGM-HF.…”
Section: Discussionmentioning
confidence: 96%
“…While sex distribution of these patients was in accordance with previous studies 35,36 and can at least partly be explained by the lower proportion of HFrEF in women, 12,37 age was again considerably increased in this patient group. 35,36 Moreover, we found that sacubitril/valsartan patients more often had diabetes mellitus and a higher weight than the other HF patients. This might be an indication for multimorbid patients having a higher chance of suffering from severe HF, consequently rendering them eligible for sacubitril/valsartan treatment.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the low blood pressure observed for sacubitril/valsartan‐treated patients (115/68 mmHg) could be a combination of the strong blood pressure‐lowering effects of sacubitril/valsartan and the severity of HF leading to sacubitril/valsartan prescription, which is often accompanied by low blood pressure. Lastly, the observed target dose achievement for sacubitril/valsartan (28.6%) was similar to the one observed in a Canadian HF clinic (27.2%) 36 but slightly lower than in a study conducted in Swiss primary care (36.5%) 39 . However, it must be considered that our study was cross‐sectional, meaning that some patients might still be in the process of up‐titration.…”
Section: Discussionsupporting
confidence: 79%
“…In the PARADIGM-HF trial [6], 42% had a reduced dose, and in the PIONEER trial [26] only 55% of the patients had the highest dose. In a real-life study by Du et al [27], at the 6month follow-up visit 27% of patients had the highest dose, 41% the mean dose and 32% the lowest dose. In elderly patients, dose reduction or discontinuation of the drug has been associated with hypotension and/or onset of renal failure.…”
Section: Limitations Of the Studymentioning
confidence: 95%